2019
DOI: 10.1523/jneurosci.1459-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Superficial Layers Suppress the Deep Layers to Fine-tune Cortical Coding

Abstract: The descending microcircuit from layer 2/3 (L2/3) to layer 5 (L5) is one of the strongest excitatory pathways in the cortex, presumably forming a core component of its feedforward hierarchy. To date, however, no experiments have selectively tested the impact of L2/3 activity on L5 during active sensation. We used optogenetic, cell-type-specific manipulation of L2/3 neurons in the barrel cortex of actively sensing mice (of either sex) to elucidate the significance of this pathway to sensory coding in L5. Contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 75 publications
10
32
0
Order By: Relevance
“…Updating our prior model to reflect this hypothesis did not significantly change the robustly observed stereotypical beta event waveform shape (10,12), and was crucial to our conclusions regarding beta event-mediated tactile suppression. Our findings are also in agreement with several studies that have suggested slow inhibition in the supragranular layers -including through GABAB mechanisms -is a key regulator of conscious perception (31,32) and is specifically involved in inhibiting somatosensory perception (33). For example, Larkum and colleagues have shown that dendrite-mediated suppression of rodent somatosensory perception is regulated by GABAB receptor activation in the mid-apical dendrite of L5 pyramidal cells, driven by a transcallosal inhibitory projection (28,34).…”
Section: Consistency Of the Current Findings With Prior Studies Of Sisupporting
confidence: 93%
“…Updating our prior model to reflect this hypothesis did not significantly change the robustly observed stereotypical beta event waveform shape (10,12), and was crucial to our conclusions regarding beta event-mediated tactile suppression. Our findings are also in agreement with several studies that have suggested slow inhibition in the supragranular layers -including through GABAB mechanisms -is a key regulator of conscious perception (31,32) and is specifically involved in inhibiting somatosensory perception (33). For example, Larkum and colleagues have shown that dendrite-mediated suppression of rodent somatosensory perception is regulated by GABAB receptor activation in the mid-apical dendrite of L5 pyramidal cells, driven by a transcallosal inhibitory projection (28,34).…”
Section: Consistency Of the Current Findings With Prior Studies Of Sisupporting
confidence: 93%
“…At a general level, our data are also compatible with this hypothesis. However, the most prominent synergy observed to date showed L2/3 suppresses deep layer activity (Adesnik & Scanziani 2010, Pluta et al 2019, predicting opposite results of deep versus superficial manipulations. We find on the contrary that mice tend to classify textures as rough when either deep or superficial layers are inhibited.…”
Section: Both Deep and Superficial Layers Are Essential For Texture Dmentioning
confidence: 97%
“…L2/3 has a strongly suppressive effect on deep layer activity (Adesnik & Scanziani 2010, Pluta et al 2019. Conceivably, strong connections like these could produce local forms of diaschisis, whereby silencing one set of layers does not reveal its task involvement but rather that it disrupts another key set of layers.…”
Section: Deep and Superficial Layers Are Critical For Texture Discrimmentioning
confidence: 99%
“…The dynamic modulation of PN firing, induced by plasticity of feed-forward inhibition had a powerful effect on the columnar integration of activity across cortical layers. Indeed, activation of layer 2/3 PNs was shown to increase the firing of PNs in layer 5 of the same column (Adesnik and Scanziani, 2010; but see Pluta et al, 2019). LTP of feed-forward inhibition strongly diminished (in fact, on average, it abolished) the layer 2/3-dependent activation of layer 5 PNs, thereby affecting the flow of neuronal communication across cortical layers.…”
Section: Discussionmentioning
confidence: 96%
“…In principle, feed-forward inhibition can result from long-range recruitment of different interneuron subclasses (Pluta et al, 2019). Yet, potentiation of FFI likely involves perisomatic inhibition originating almost exclusively from PV basket cells.…”
Section: Discussionmentioning
confidence: 99%